Upaya Meningkatkan Hasil Belajar Matematika Menggunakan Metode Mind Map pada Siswa Kelas V SD Negeri 38 Ampenan - Nurhasanah Nurhasanah (Jurnal Teknologi Pendidikan : Jurnal Penelitian dan Pengembangan Pembelajaran, 2021)
The purpose of this study was to improve student learning outcomes in mathematics learning by using the mind map method for fifth grade students of SD Negeri 38 Ampenan. The research method used is classroom action research. The research process used was the research proposed by Kemmis and Taggart which used a spiral system cycle, each cycle consisting of planning, action, observation, and reflection. The subjects in this study were 37 grade V SD Negeri 38 Ampenan students. Research data obtained from the results of observations, tests and documentation. The data analysis technique used descriptive qualitative and quantitative. The results showed that the students' mathematics learning outcomes using the Mind Map method had increased. This is indicated by an increase in the average mathematics learning outcomes of grade V students by 49.01%. In addition, the results of the analysis of the observation data increased from 46.7% of the fulfilled aspects to 86.7% of the aspects.